Dimensi perlindungan konsumen dalam hukum positif Indonesia - Wiesna, Dira Nabilah (Maliki Interdisciplinary Journal, 2023)
The Consumer Protection Law is a law that protects consumers and business actors providing goods and services. The Consumer Protection Law is an inmportant Law is an important law because transactions in society have become activities in everyday life. The law aims to protect and guarantee the ongoing transactions that become daily activities in social life. The Consumer Protection Law takes the form protecting consumer security, protecting the right to obtain information, the right to choose for consumers, preventing business actors that are prohibited by law and so on. Consumer Protection Law is related to Civil Law and Public Law such as Criminal Law and State administrative Law.